2018
DOI: 10.3389/fphys.2018.01053
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Specific “Competition for Calories” Drives Asymmetric Nutrient-Energy Partitioning, Obesity, and Metabolic Diseases in Human and Non-human Animals

Abstract: The mammalian body is a complex physiologic “ecosystem” in which cells compete for calories (i.e., nutrient-energy). Axiomatically, cell-types with competitive advantages acquire a greater number of consumed calories, and when possible, increase in size and/or number. Thus, it is logical and parsimonious to posit that obesity is the competitive advantages of fat-cells (adipocytes) driving a disproportionate acquisition and storage of nutrient-energy. Accordingly, we introduce two conceptual frameworks. Asymmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 261 publications
(585 reference statements)
0
35
0
Order By: Relevance
“…Nevertheless, a number of the studies failed to include important potential confounders and effect modifiers. These include race, ethnic, or religious affiliation, social norms, as well as lifestyle behaviors that directly affect health (e.g., smoking, and alcohol use) and the physiologic determinants of dietary energy intake (e.g., physical activity, body cellularity; Archer 2018b; Archer, Lavie, and Hill 2018a;Archer et al 2018e). Given that when compared to the general population, individuals who follow a vegetarian diet tend to be more health-conscious, more physically active, more highly educated, consume less alcohol, be nonsmokers and have higher socio-economic status Chang-Claude et al 2005), it is essential for future studies to include detailed information on participants' health and behavioral histories and current characteristics.…”
Section: Duration Of Dietary Patternsmentioning
confidence: 99%
“…Nevertheless, a number of the studies failed to include important potential confounders and effect modifiers. These include race, ethnic, or religious affiliation, social norms, as well as lifestyle behaviors that directly affect health (e.g., smoking, and alcohol use) and the physiologic determinants of dietary energy intake (e.g., physical activity, body cellularity; Archer 2018b; Archer, Lavie, and Hill 2018a;Archer et al 2018e). Given that when compared to the general population, individuals who follow a vegetarian diet tend to be more health-conscious, more physically active, more highly educated, consume less alcohol, be nonsmokers and have higher socio-economic status Chang-Claude et al 2005), it is essential for future studies to include detailed information on participants' health and behavioral histories and current characteristics.…”
Section: Duration Of Dietary Patternsmentioning
confidence: 99%
“…And more importantly, the effects of dietary intake are entirely dependent on the physiologic context of the consuming individual ( 15 ). Thus, with respect to diet-related health, it is not what is eaten that affects health and disease, but what one's body does with what was eaten ( 113 , 114 ). Therefore, as we previously detailed ( 15 , 55 , 113 ), the idea that “you are what you eat” is demonstrative of prescientific thinking [i.e., magico-religious reasoning ( 55 )], “physiologic illiteracy” ( 15 , 114 ), and flouts centuries of progress in medical science because dietary components cannot have effects independent of the physiologic context of the consuming individual ( 15 , 55 , 113 , 114 ).…”
Section: Challenges and Relevancy Of Estimating Dietary Intakementioning
confidence: 99%
“…For a review please see ( 15 , 113 ). Finally, research dating to the 1950s demonstrated that the “over-consumption” that leads to obesity and metabolic disease is not driven by dietary factors per se , but by physical inactivity-induced increments in energy intake ( 113 , 114 , 131 134 ) and non-genetic evolutionary processes (i.e., accumulative maternal effects) ( 113 , 114 , 135 137 ) that lead to the asymmetric and adipogenic partitioning of nutrient-energy ( 114 ).…”
Section: Challenges and Relevancy Of Estimating Dietary Intakementioning
confidence: 99%
“…Although the current evidence has been questioned by some studies [58,64,108], the data in the literature are accumulating in support of the potential role of epigenetic and genetic patterns of parents in offspring health. Therefore, comprehensive knowledge of the epigenetic modifications induced by unhealthy parental lifestyles or by exposure to environmental insults in the periconceptional period could provide useful insights for the prevention of long-term disease in the offspring.…”
Section: Future Perspectivesmentioning
confidence: 98%
“…The maternal resources hypothesis proposes a novel conceptualization of inheritance and evolution, in which non-genetic vectors, including accumulative maternal effects (i.e., maternal prenatal energy metabolism and maternal postnatal physical activity), socio-environmental and phenotypic evolution, are the predominant causal factors for the health of future generations [62]. Thus, in this evolutionary context, the "overconsumption" that leads to metabolic disease is due not to dietary factors per se, but rather to physical inactivity caused by increments in energy intake and non-genetic evolutionary processes with the adipogenic partitioning of nutrient-energy [62][63][64].…”
Section: Other Viewpointsmentioning
confidence: 99%